2019
DOI: 10.1089/mdr.2018.0046
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Molecular Characterization of Extended-Spectrum β-Lactamases ofEscherichia coliandKlebsiellaspp. Isolates from Urinary Tract Infections in Southern Brazil

Abstract: The objective of this study was to evaluate the frequency of different extended-spectrum β-lactamases (ESBL) as well as to associate these ESBL with antimicrobial (ATM) resistance in Escherichia coli and Klebsiella spp. isolates from outpatients and inpatients with urinary tract infections. The study included 435 consecutive nonduplicate clinical isolates, including 362 E. coli isolates, 62 Klebsiella pneumoniae isolates, and 11 K. oxytoca isolates. Isolates were obtained from patients who were treated in a Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 43 publications
5
8
3
1
Order By: Relevance
“…1. Similar results were described by Pereira et al (2019) who evaluated E. coli (362 strains) and Klebsiella spp. (73 strains) isolated from urinary tract infections in southern Brazil, which demonstrated high percentage of resistance in 91.3% (n = 21/23) antimicrobials analysed: ampicillin (AMP), ampicillin-sulbactam (APS), piperacillin-tazobactam (PIT), amoxicillin-clavulanate (AMC), cefazolin (CFZ), cefotaxime (CTX), ceftazidime (CAZ), ceftriaxone (CRO), cefuroxime (CRX), cefepime (CPM), cefoxitin (CFO), aztreonam (ATM), ertapenem (ERT), meropenem (MPM), imipenem (IPM), amikacin (AMI), tobramycin (TOB), nitrofurantoin (NIT), sulfamethoxazole (SUT), tetracycline (TET), ciprofloxacin (CIP), levofloxacin (LEV).…”
Section: Resultssupporting
confidence: 83%
“…1. Similar results were described by Pereira et al (2019) who evaluated E. coli (362 strains) and Klebsiella spp. (73 strains) isolated from urinary tract infections in southern Brazil, which demonstrated high percentage of resistance in 91.3% (n = 21/23) antimicrobials analysed: ampicillin (AMP), ampicillin-sulbactam (APS), piperacillin-tazobactam (PIT), amoxicillin-clavulanate (AMC), cefazolin (CFZ), cefotaxime (CTX), ceftazidime (CAZ), ceftriaxone (CRO), cefuroxime (CRX), cefepime (CPM), cefoxitin (CFO), aztreonam (ATM), ertapenem (ERT), meropenem (MPM), imipenem (IPM), amikacin (AMI), tobramycin (TOB), nitrofurantoin (NIT), sulfamethoxazole (SUT), tetracycline (TET), ciprofloxacin (CIP), levofloxacin (LEV).…”
Section: Resultssupporting
confidence: 83%
“…Our results showed that 48 strains are resistant to imipenem, meropenem, and ertapenem in which 15.6% was positive for IMP, 2.42% for VIM, and 1.92% positive for NDM-1 gene. Some studies showed that, with respect to the relative increase in resistance, ciprofloxacin and its derivatives such as quinolone, Amikacin such as aminoglycoside, and Imipenem such as beta-lactam have been the most effective antibiotics for the treatment of Pseudomonas infections [22][23][24]. In our study, the most effective aminoglycoside, quinolone, and beta-lactam were tobramycin, ciprofloxacin, and imipenem, respectively.…”
Section: Methodssupporting
confidence: 48%
“…In India, the most prevalent MRSA is SCC mec type III, corresponding to 58% of the isolates [ 20 ]. In Brazil, 65.4% of MRSA are type II, 37% type I, and 15.4% type IV [ 27 , 28 ], and in the United States 29.9% are type II and 30.9% are type IV [ 29 ].…”
Section: Antibiotic-resistant Strainsmentioning
confidence: 99%
“…In North America, ESBL-producing Enterobacterales have been more prevalent in the US, in which a study conducted between 2013 and 2017 with 1.112.312 enterobacterial isolates from 411 US hospitals found that about 12.05% were producers ESBL [ 65 ], with the CTX-M class being the most widespread in that country [ 97 ]. In Brazil, a study conducted with 435 isolates of enterobacteria from the southeast region of the country, showed that 48 isolates (11%) were ESBL producers, with the bla CTX-M-1 and bla CTX-M-8/25 genes being the most found in samples, as well as combinations of CTX-M, TEM, SHV and OXA [ 28 ].…”
Section: Extended-spectrum β-Lactamase-producing Enterobact...mentioning
confidence: 99%